The Regenerating Gene Iα Is Overexpressed in Atrophic Gastritis Rats with Hypergastrinemia. (1st August 2011) - Chen, Shujie; Zhong, Jing; Zhou, Qunyan; Lu, Xiaofeng; Wang, Liangjing; Si, Jianmin
Abstract : The role of gastrin on the development of atrophic gastritis (AG) and its relationship with the expression of RegI α in vivo remain unclear. We established experimental AG in rats by combination administration with sodium salicylate, alcohol, and deoxycholate sodium. The mean score of inflammation in gastric antrum in AG rats was significantly elevated (P < 0.05 ), while the number of glands dramatically decreased (P < 0.05 ). In addition, the cell proliferation in gastric glands was increased in experimental AG rats, as determined by immunohistochemistry staining of PCNA and GS II. The level of serum gastrin in AG rats was significantly elevated relative to that of normal rats (P < 0.01 ). Moreover, the expression of RegI α protein and its receptor mRNA was increased in gastric tissues in AG rats (P < 0.05 ). Taken together, we demonstrated that the overexpression of Regl α is related with hypergastrinemia in AG rats.